Pengaruh Pendekatan Pembelajaran Berbasis Proyek terhadap Kemandirian Anak Kelompok B di TK Negeri Harmonis Kecamatan Tapa - Putri M Halim; Rapi Us Djuko; Sri Wahyuningsi Laiya (Simpati, 2026)
This study aims to determine the effect of the project-based learning approach on the independence of Group B children at TK Negeri Harmonis, Tapa District. The study employed a quantitative approach using a pre-experimental method with a one-group pretest-posttest design. The subjects consisted of 9 Group B children (3 boys and 6 girls) determined through total sampling. Data were collected through observation using an instrument of 11 statement items covering four indicators of independence, and were analyzed using validity testing (product moment correlation), reliability testing (Cronbach's Alpha), the Shapiro-Wilk normality test, and hypothesis testing using the paired sample t-test. The results showed that the mean pretest score was 20.22 (SD = 4.76) and increased to 30.00 (SD = 5.72) in the posttest. The paired sample t-test obtained a t-value of 11.131 with a significance value of <0.001 (p < 0.05), so that H0 was rejected and H1 was accepted, indicating a significant effect of the project-based learning approach on children's independence. The novelty of this research lies in its focus on Group B children at TK Negeri Harmonis, Tapa District, a research setting that has rarely been examined, thereby providing empirical evidence on the effectiveness of project-based learning in developing early childhood independence.